Head and neck cancer associated with increased rate of pulmonary tuberculosis in a population-based cohort study. Issue 43 (October 2017) - Lai, Shih-Wei; Lin, Cheng-Li; Liao, Kuan-Fu
Abstract : Abstract: The objective of this study was to examine the incidence and hazard ratio (HR) of pulmonary tuberculosis in patients with head and neck cancer in Taiwan. This population-based retrospective cohort study was conducted to analyze the database of the Taiwan National Health Insurance Program. There were 2522 subjects aged 20 to 84 years with newly diagnosed head and neck cancer as the head and neck cancer group between 2000 and 2012, and 10, 064 randomly selected sex- and age-matched subjects without any cancer as the noncancer group. The incidence of pulmonary tuberculosis at the end of 2013 was estimated in both groups. A multivariable Cox proportional hazards regression model was used to estimate the HR and 95% confidence interval (CI) for pulmonary tuberculosis being associated with head and neck cancer. The overall incidence of pulmonary tuberculosis was 2.86-fold greater in the head and neck cancer group than that in the noncancer group (4.70 vs 1.64 per 1000 person-years, 95% CI, 2.53–3.24). After adjusting for confounding factors, the adjusted HR of pulmonary tuberculosis became 2.90 for the head and neck cancer group (95% CI, 2.11–3.99), compared with the noncancer group. In addition, male (adjusted HR 2.27, 95% CI, 1.29–4.00) and age (increase for 1 year, adjusted HR 1.06, 95% CI, 1.05–1.08) were associated with pulmonary tuberculosis. Head and neck cancer is significantly associated with 2.90-fold increased hazard of pulmonary tuberculosis in Taiwan, compared with the general population.